2017
DOI: 10.1016/j.nicl.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural abnormalities in white and gray matter in obese adolescents with and without type 2 diabetes

Abstract: Aims/hypothesesIn adults, type 2 diabetes and obesity have been associated with structural brain changes, even in the absence of dementia. Some evidence suggested similar changes in adolescents with type 2 diabetes but comparisons with a non-obese control group have been lacking. The aim of the current study was to examine differences in microstructure of gray and white matter between adolescents with type 2 diabetes, obese adolescents and healthy weight adolescents.MethodsMagnetic resonance imaging data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 54 publications
2
74
0
Order By: Relevance
“…Lower MWF in relation to higher insulin and IR was largely localized to posterior brain regions, while higher MWF in relation to higher insulin and IR was primarily observed in frontal, parietal, and temporal cortical brain regions (Figures 2,3). Posterior localization of white matter abnormalities has also been observed among individuals with mild cognitive impairment (38) and other aging populations (39), while several of these regions were shown to be altered in type II diabetes (40). We and others have also shown frontal and temporal white matter regions to exhibit extensive white matter alterations in aging populations (9-11); however, less is known about how myelinated fibers of these regions, particularly within the cortex, are affected by insulin and IR.…”
Section: Discussionmentioning
confidence: 94%
“…Lower MWF in relation to higher insulin and IR was largely localized to posterior brain regions, while higher MWF in relation to higher insulin and IR was primarily observed in frontal, parietal, and temporal cortical brain regions (Figures 2,3). Posterior localization of white matter abnormalities has also been observed among individuals with mild cognitive impairment (38) and other aging populations (39), while several of these regions were shown to be altered in type II diabetes (40). We and others have also shown frontal and temporal white matter regions to exhibit extensive white matter alterations in aging populations (9-11); however, less is known about how myelinated fibers of these regions, particularly within the cortex, are affected by insulin and IR.…”
Section: Discussionmentioning
confidence: 94%
“…Reduced activity in the caudate nuclei is associated with obesity in older adults (Green, Jacobson, Haase, & Murphy, 2011). Additionally, adolescents with T2DM have been found to exhibit reduced GMV in the caudate nuclei compared to metabolically healthy age-and weight-matched controls (Nouwen et al, 2017).…”
Section: The Appetitive Networkmentioning
confidence: 99%
“…In the last few years, an increased body of evidence has emerged on obesity-related comorbidities and metabolic alterations and their relationship with structural brain abnormalities in children and adolescents [9,[34][35][36]. For instance, Perlaki et al [36] showed that a higher degree of obesity was associated with greater volumes in the amygdala and accumbens, regions involved in the food rewards.…”
Section: Discussionmentioning
confidence: 99%